The Impact of Artificial Intelligence on Accounting Information Systems in Jordanian Banks: An Exploratory Study - Maha Abuyabes; Ahmad Alshekhhossin; Ishraq Bataineh (تنمیة الرافدین)
Artificial intelligence (AI) has become one of the critical technological tools for enhancing the efficiency and quality of accounting operations, minimising human errors, and accelerating data analysis and decision-making processes. Thus, the purpose of the study is to explore the impact of AI on accounting information systems(AIS) within Jordanian banks. The study proposed a research model based on the related studies. A quantitative approach was employed, using a questionnaire for data collection. The sample consisted of staff from the financial services and audit departments of 15 Jordanian banks, including financial managers, internal auditors, heads of accounts, and accountants. Several statistical methods are used for data analysis, SEM  was applied for data analysis using smartpls tool. The study found that AI has a considerable impact on the AIS system.  In order to reap the benefits of AI, the study advises Jordanian banks to implement cutting-edge technologies based on AI and machine learning to improve accounting system performance. It is recommended that further research be conducted to get a more in-depth understanding of the variables influencing the interaction between AI and the accounting information systems of banks.